دراسة الآثار في تفسير حُسن البيان للشيخ محمد طه الباليساني وموقفه منها دراسة نقدية حديثية - باوه, أ.د.صلاح الدين عبدالله; عزيز, محمد أحمد (Sulaimani Journal for Humanities, 2023)
The sayings of the Companions, known to scholars as "Athar", have a prominent role in clarifying the Qur'anic verses and their interpretation. Scholars, both ancient and modern, have relied on it in all Islamic sciences, especially the commentators, as they cited, during their interpretation of the Qur'anic verses, dozens of traces within the framework of interpreting the Qur'an with the sayings of the Companions and Folowers.These are the scholar-interpreter Sheikh Muhammad Taha al-Balisani, who embellished his interpretation with the sayings of the Companions and the followers and the follower of the followers(the honorable antiguities).The Noble One is based on the sayings of the Companions, the Followers, and their followers, and the Companions are considered among the first class of the mujtahids in interpretation after the Messenger of God-may God's prayers and peace be upon him. Their interpretation has an advantage over the interpretation of those who came after them.